2006
DOI: 10.1146/annurev.physchem.57.032905.104538
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Chemical Dynamics in Gases and Liquids

Abstract: Modern ultrafast spectroscopic techniques provide new opportunities to study chemical reaction dynamics in liquids and hold the possibility of obtaining much of the same detailed information available in gases. Vibrational energy transfer studies are the most advanced of the investigations and demonstrate that it is possible to observe state-specific pathways of energy flow within a vibrationally excited molecule (intramolecular vibrational relaxation) and into the surrounding solvent molecules (intermolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
151
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 126 publications
3
151
0
Order By: Relevance
“…12,23 Recently, it has even been suggested that solute/solvent interactions which take place in the course of transient vibrational relaxation dynamics provide a route to enantioselective amplification. 19 Accurately simulating reaction dynamics in coupled solute/solvent environments remains a challenge within the field of computational and theoretical chemistry, 14,16,[24][25][26] mostly owing to the fact that it is difficult to construct a potential energy surface (PES) whose balanced accuracy and efficiency is sufficient to interpret experiments. Further complications arise according to the fact that experimental dynamic observables ultimately derive from the quantum mechanical properties of molecules, but efficient methods for carrying out full quantum mechanical dynamics simulations of condensed phase systems are not generally available.…”
Section: Introductionmentioning
confidence: 99%
“…12,23 Recently, it has even been suggested that solute/solvent interactions which take place in the course of transient vibrational relaxation dynamics provide a route to enantioselective amplification. 19 Accurately simulating reaction dynamics in coupled solute/solvent environments remains a challenge within the field of computational and theoretical chemistry, 14,16,[24][25][26] mostly owing to the fact that it is difficult to construct a potential energy surface (PES) whose balanced accuracy and efficiency is sufficient to interpret experiments. Further complications arise according to the fact that experimental dynamic observables ultimately derive from the quantum mechanical properties of molecules, but efficient methods for carrying out full quantum mechanical dynamics simulations of condensed phase systems are not generally available.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Many of these studies have concentrated on radical reactions in the gas phase. Under gas-phase conditions dominated 3 by isolated collisions, competing reaction pathways can be distinguished, as can the release of excess energy from exothermic reactions into specific translational, rotational, vibrational or electronic degrees of freedom of the reaction products. These types of observation reveal detailed information about the structures of key intermediates along the reaction path.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the surrounding solvent interacts continuously with the reacting species and can modify energy barriers, reaction pathways, product yields and the flow of any energy released. 3 These interactions occur on ultrafast (femtosecond to picosecond) timescales, but non-equilibrium reaction dynamics reminiscent of the gas-phase can persist if reactive events are fast enough to compete with the response of the surrounding solvent. [4][5][6][7][8] To investigate some of the effects of solvent on the dynamics and pathways of bimolecular reactions, ultraviolet (UV) photolysis of dissolved cyanogen iodide (ICN) has been employed as a source of CN radicals.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] The present study has two aims: to gain new and direct insight into this important reaction (extracting quantum yields of intermediate and product formation wherever possible) and to illustrate the role of contemporary ultrafast transient absorption spectroscopy methods in unravelling mechanistic details of a classic photoinduced organic reaction.…”
Section: Introductionmentioning
confidence: 99%